Influence of transient conditions on thermal comfort evaluations: Field study in university buildings - Keovathana Run; Franck Cévaër; Jean-François Dubé (Case Studies in Thermal Engineering)
Thermal comfort is directly associated with the user’s health, performance, and energy consumption, making it a focal point of attention over the years. The static model heavily relies on the thermally steady state to assess thermal comfort. However, thermal conditions in buildings are rarely steady, particularly in university buildings where students move from one class to another after each session. While this issue has been discussed previously, those studies are lab-based experiments that lack realistic settings. Aiming to address this gap, this paper conducted a field study in the university buildings under Mediterranean weather conditions during the winter and summer. To create transient-state and steady-state datasets, random groups of participants completed questionnaire surveys at various time points. These data were used to compare with previous climate chamber studies on temporal changes and to evaluate Fanger’s model. The results revealed that students took less than 10 min to reach a thermally steady state with a mere 0.5 scale points difference in thermal sensation vote between the two states. Moreover, the difference between the thermal sensation vote and the predicted mean vote models was potentially due to the assumed parameters rather than the effect of different thermal states on the calculations. Nevertheless, no substantial difference was noted for the neutral and preferred temperatures between the two conditions. These findings suggested that, in field studies, data collected from short-term thermal experience performed reasonably well in estimating comfort temperatures. The calculations’ assumptions, however, remained a limitation of this paper.